Numerical Analysis of the Age-Sex-Structured Population Dynamics Taking into Account Spatial Diffusion - Repšys, Š.; Skakauskas, V. (Nonlinear Analysis: Modelling and Control, 2005)
We present results of the numerical investigation of the homogenous Dirichlet and Neumann problems to an age-sex-structured population dynamics deterministic model taking into account random mating, female’s pregnancy, and spatial diffusion. We prove the existence of separable solutions to the non-dispersing population model and, by using the numerical experiment, corroborate their local stability.
Keywords: age-sex-structured population; child care; spatial diffusion